Main Problems of Military-Professional Activity Orientation of Young Students - Mamadalimov Azimjon Hasanboyevich; Mamazhonov Soyibjon Khalilovich; Toshpulatov Abrorjon Mirhokimovich (Periodica Journal, 2022)
This articleюdeals with the development of the education system and upbringing of the young generation, touches upon the conceptual foundations of reforming the system of personnel training and education, indicates the problems in the possibility of full implementation of the human factor in strengthening the educational capacityof our country, and also focuses on the dependence of military professional orientation on the quality of work of the head of the DPJ educational institution.
Keywords: Conceptual framework; person; youth orientation; head of DPJ